Pengaruh Kepemimpinan, Lingkungan Kerja Fisik dan Kompensasi terhadap Kinerja Karyawan - Arifin, Theo (JRMA | Jurnal Riset Manajemen dan Akuntansi, 2015)
This study aimed to test the significance of the effect of transactional leadership, transformational leadership, physical work environment, and compensation partially or simultaneously on employee performance. The population in this study were permanent employees of PT Bank BRI Branch Office Madiun totaling 55 people, all members of the population that is the subject of research. The results of t-test showed that transactional leadership factors had no significant effect on employee performance. Transformational leadership factors, physical work environment, and compensation significant effect on the performance of employees. F test showed that the factor of transactional leadership, transformational leadership, physical work environment, and compensation simultaneously significant effect on employee performance. Based on this research the companies need to further emphasize transactional leadership, in addition to taking into account the transformational leadership, physical work environment, and the compensation that will affect the performance of the employees become better.